(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article is devoted to study the role of translation and the translator’s work in the analysis of the setting in the literary work, and the level of this influence in J. K. Rowling’s novel "Harry Potter and the Sorcerer’s Stone" (“Гарри Поттер и философский камень”, “Garri Potter va falsafiy tosh”). During the research, these books were analyzed not as three translations of one work, but as separate works by three different authors, and then the conclusions were compared. As a result, it has been proven that every translator has his own style, that this style, like many other aspects, affects the content of the work and makes the translator a co-author of this work in some sense. Although there are some substantive flaws in both translations, none of them should be considered completely wrong or inaccurate, because these examples of creativity reflect the imaginations of not only Joanna Rowling, but also Marina Litvinova, Maria Spivak and Shakir Dolimov. This is the reason why the setting was chosen for the analysis, because one place can be seen by ten pairs of eyes in ten different ways.